The Use of Dragon Fruit and Pineapple as Food and Traditional Medicine, and Their Potential as Food to Prevent Stunting - Gharsina Ghaisani Yumni; Ulfa Filliana (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2025)
Many tropical countries, including Indonesia, grow dragon fruit (Hylocereus polyrhizus) and pineapple (Ananas comosus). Both of them have a lot of vitamins, minerals, bioactive compounds, and fiber in their diets. Flavonoids, phenolics, betalain pigments (from dragon fruit), and the enzyme bromelain (from pineapple) are some of the bioactive compounds that give these foods their antioxidant properties and possible health benefits. Studies show that eating pineapple and dragon fruit, as well as foods made from them, can raise antioxidant levels, reduce inflammation, fight bacteria, and protect against some degenerative diseases. People have eaten both fruits a lot in the past as fresh food, drinks, jams, and dodol. They have also been used in traditional medicine for digestive problems, inflammation, and the immune system. Dragon fruit and pineapple contain bioactive compounds and antioxidants that may support children's gut health and nutrition, as oxidative stress, chronic inflammation, and nutritional imbalances can all lead to stunting. In this literature review, we examine the chemical composition, antioxidant characteristics, and customary applications of dragon fruit and pineapple. We also look into how these fruits could be used as functional foods to help stop stunting.